Makna Semantik Qalbu dalam Al-Qur'an - Ahmad Dibul Amda; Mirzon Daheri (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2020)
This research aims to examine the true meaning of qalb (heart) in the Qurâ€™an. This is important to understand because qalb (heart) is said to be something that is very vital in determining oneâ€™s value. This literature research was carried out using a thematic interpretation approach (Ø§Ù„Ù€ØªÙ€ÙÙ€Ù€Ø³Ù€Ù€ÙŠÙ€Ù€Ø± Ø§Ù„Ù…Ù€Ù€ÙˆØ¶Ù€Ù€ÙˆØ¹Ù€Ù‰). The analysis technique used is content analysis. From the results of this study, it is known that there are two semantic meanings of the heart in the Qurâ€™an, physically and psychologically. Physically it is the heart, while psychologically the heart (qalb) or shadr is the spirit as human essence. It becomes the main motor in human movement, a place for faith to be entrusted.